Regenerasi dan Aklimatisasi Kultur Antera Enam Persilangan F1 Padi Sawah - Gunarsih, Cucu; Purwoko, Bambang Sapta; Dewi, Iswari Saraswati; Syukur, dan Muhamad (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
ABSTRACTThe breeding of rainfed rice tolerant to drought can be accomplished using anther culture. The objectives of this research were to determine regeneration abilities of six F1 anther culture and its acclimatization ability. The experiment was arranged in completely randomized design with 14 replications. The treatments consisted of six F1 derived from crossing:  INPARI 18 x IR83140-B-11-B (G1), INPARI 18 x B12825E-TB-1-25 (G2), INPARI 18 x IR87705-14-11-B-SKI-12 (G3), INPARI 22 x IR83140-B-11-B (G4), Bio-R81 x O18b-1 (G5), Bio-R82-2 x O18b-1 (G6). Media for callus induction was based on N6 medium + 2.0 mg L-1 NAA + 0.5 mg L-1 kinetin + 1.0 mM putresin + 60 g L-1 sucrosa, media for regeneration was based on MS + 0.5 mg L-1 NAA + 2.0 mg L-1 kinetin + 1.0 mM  putresin, and media for rooting was based on  MS + 0.5 mg L-1 IBA + 30 g L-1 sucrosa. The result indicated that all six F1 had different ability in anther culture. Bio-R82-2 x O18-b1 (G6) and  Bio-R81 x O18-b1 (G5) F1 genotype had good response both of callus induction and plant regeneration. These two F1 genotypes also gave the highest ratio of green planlet production to number of anther inoculated (GP:AI) were 5.50% and 4.65%,  respectively. In this research, there were identified doubled haploid plants were developed from 4 F1 derived cross namely G2 (2 plants), G3 (4 plants),  G5 (21 plants), and G6 (26 plants).Keywords: Callus induction, doubled haploid, rice